2016
DOI: 10.3747/co.23.3181
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Phase Angle as a Prognostic Indicator of Survival in Head-and-Neck Cancer

Abstract: Background Phase angle could be an alternative to subjective global assessment for the assessment of nutrition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The median PA at diagnosis for all patients was 5.91°, which was similar as in a previous study of mixed cancer patients with a median PA at 5.95° [29]; however, in two studies, one on breast cancer [15] and one on colorectal cancer [30], the median PA was lower at 5.6°; and one study on patients with HN cancer identified a lower mean PA of 5.04° [31]. In the current study, PA was a significant prognostic factor for survival at uni- and multivariable analyses.…”
Section: Discussionsupporting
confidence: 83%
“…The median PA at diagnosis for all patients was 5.91°, which was similar as in a previous study of mixed cancer patients with a median PA at 5.95° [29]; however, in two studies, one on breast cancer [15] and one on colorectal cancer [30], the median PA was lower at 5.6°; and one study on patients with HN cancer identified a lower mean PA of 5.04° [31]. In the current study, PA was a significant prognostic factor for survival at uni- and multivariable analyses.…”
Section: Discussionsupporting
confidence: 83%
“…BIA was demonstrated to correlate with the results obtained from DXA and magnetic resonance tomography [ 34 , 72 , 73 ]. Investigations estimating the reliability of measured body composition parameters by BIA and the wide application range of this technology, also in cancer patients, warranted the use within our study [ 50 , 74 , 75 ]. A huge advantage of the seca instrument that we used in this study is that BIA can be performed easily and very quickly by clinical staff, without distressing patients by elaborated and time-consuming measurement techniques or exposing them to X-rays [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…PhA is used as an indicator of cellular health in relation to imbalance of cellular water and integrity of the cell membrane [8]. However, the PhA value can be negatively influenced by several clinical diseases, such as malnutrition [9], diabetes [10], human immunodeficiency virus infection (HIV infection) [11], and some types of cancer [12,13]. Healthy individuals show higher values of PhA (higher than 5º), indicating better cellular health and cell membrane integrity compared to malnourished patients [9].…”
Section: Introductionmentioning
confidence: 99%